ANALISIS PENERAPAN TARIF PROGRESIF PAJAK KENDARAAN BERMOTOR PADA UNIT PELAKSANA TEKNIS DAERAH (UPTD) KOTA MANADO - Thomas, Mario Y.; Saerang, David P. E.; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Vehicle Tax is the major contributor to the Original Local Government Revenue, with a progressive tax rate. Vehicle is a crucial asset because the price per unit is relatively high. The tax function fulfillment in this policy is very influential to the wealth of people as a vehicle user, whether it is for entrepreneur or non-entrepreneur. Every province is unique by economy, social, cultural and other factors that are obviously differentiating the tax policy implementation. This research analyzes the implementation of vehicle progressive tax rate policy in Manado City Local Technical Operating Unit and explains the obstacles faced along with the efforts to overcome. This research is done by the qualitative approach with descriptive analysis. Research result describes the policy implementation specifically by some aspects related to vehicle tax, explains the obstacles faced along with the efforts to overcome.Keywords : progressive tax rate, vehicle tax